Pemberdayaan Masyarakat Melalui GURU CIKA (Guyub Rukun Cegah dan Atasi KEK dan Anemia) Pada Remaja dan Ibu Hamil di Desa Purworejo Kabupaten Blora - Yanik Muyassaroh; Anjar Astuti; Marlynda Happy Nurmalita Sari (Poltekkes Kemenkes Semarang, 2023)
According to the World Health Organization (WHO), the highest percentage causes of maternal death are bleeding (28%) and infection, which can be caused by low hemoglobin (Hb) levels or anemia and chronic energy deficiency (CED). Prevention efforts that can be carried out before pregnancy are prioritized from adolescence so that the actions taken can provide optimal results. This activity aims to increase the knowledge of teenagers and pregnant women about preventing anemia and CED. The activity was carried out through counseling through the emotional demonstration method to 20 pregnant women and 20 young women. Assessment of the target's level of knowledge in preventing anemia and CED was carried out before and after counseling through a questionnaire containing closed questions. The Wilcoxon test is used to analyze the mean difference between the two assessment results. The results of this activity showed an increase in knowledge of adolescents and pregnant women about the fulfillment of nutrition and prevention of SEZs and Anemia after counseling using the emotional demonstration methodKeyword: adolescents, pregnant women, SEZ, anemia